2016
DOI: 10.1080/02640414.2016.1156728
|View full text |Cite
|
Sign up to set email alerts
|

Support leg action can contribute to maximal instep soccer kick performance: an intervention study

Abstract: 20This investigation assessed whether a Technique Refinement Intervention designed to 21 produce pronounced vertical hip displacement during the kicking stride could improve 22 maximal instep kick performance. Nine skilled players (age 23.7 ± 3.8 years, height 23 1.82 ± 0.06 m, body mass 78.5 ± 6.1 kg, experience 14.7 ± 3.8 years; mean ±SD) 24 performed 10 kicking trials prior to (NORM) and following the intervention (INT). 25Ground reaction force (1000Hz) and three-dimensional motion analysis (250Hz)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 31 publications
1
17
0
5
Order By: Relevance
“…However, these findings are in contrast to [42,[47][48][49], who reported a more extended support leg knee was correlated to larger foot speeds for kicking distance. Also in [37,50,51] lifting the whole-body upward through the motion of the support leg (through knee extension) has been identified as an effective action to help generate faster foot speed's through achieving a more extended kick-leg (and hence a longer lever arm) during the swing phase .…”
Section: Discussionmentioning
confidence: 99%
“…However, these findings are in contrast to [42,[47][48][49], who reported a more extended support leg knee was correlated to larger foot speeds for kicking distance. Also in [37,50,51] lifting the whole-body upward through the motion of the support leg (through knee extension) has been identified as an effective action to help generate faster foot speed's through achieving a more extended kick-leg (and hence a longer lever arm) during the swing phase .…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have reported that when kicking distance increases, players are required to increase foot speed and ball speed accordingly, in order to meet the distance demand [ 3 , 6 , 11 , 53 ]. Lifting the whole-body upward through the motion of the support-leg (through knee extension) has been identified as an effective action to help generate faster foot speed’s through achieving a more extended kick-leg (and hence a longer lever arm) during the swing phase [ 7 , 51 , 54 ]. This explanation is partly supported by the higher foot speed’s (18.0 m.s -1 ) reported in this study compared those reported from Blair et al [ 9 ] (13.2 m.s -1 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, a limitation of these findings is that they consider the kick leg independent from the rest of the body (Lees et al, 2010). More recent evidence suggests that the support leg, pelvis and torso also all contribute to kicking performance (Augustus et al, 2017;Fullenkamp et al, 2015;Inoue et al, 2014;Naito et al, 2010). Pelvis rotations about the support leg may precede kick leg sequencing (Inoue et al, 2014;Lees et al, 2009), and concentric work performed at the support knee (Augustus et al, 2017) and torso (Naito et al, 2010) may serve to extend the kicking knee later in the downswing.…”
Section: Introductionmentioning
confidence: 99%
“…More recent evidence suggests that the support leg, pelvis and torso also all contribute to kicking performance (Augustus et al, 2017;Fullenkamp et al, 2015;Inoue et al, 2014;Naito et al, 2010). Pelvis rotations about the support leg may precede kick leg sequencing (Inoue et al, 2014;Lees et al, 2009), and concentric work performed at the support knee (Augustus et al, 2017) and torso (Naito et al, 2010) may serve to extend the kicking knee later in the downswing. Unfortunately, to date, energy transfers between these segments have only been inferred indirectly.…”
Section: Introductionmentioning
confidence: 99%